Fracture Rates and Lifetime Estimations of CAD/CAM All-ceramic Restorations. (January 2016) - Belli, R.; Petschelt, A.; Hofner, B.; Hajtó, J.; Scherrer, S.S.; Lohbauer, U.
The gathering of clinical data on fractures of dental restorations through prospective clinical trials is a labor- and time-consuming enterprise. Here, we propose an unconventional approach for collecting large datasets, from which clinical information on indirect restorations can be retrospectively analyzed. The authors accessed the database of an industry-scale machining center in Germany and obtained information on 34, 911 computer-aided design (CAD)/computer-aided manufacturing (CAM) all-ceramic posterior restorations. The fractures of bridges, crowns, onlays, and inlays fabricated from different all-ceramic systems over a period of 3.5 y were reported by dentists and entered in the database. Survival analyses and estimations of future life revealed differences in performance among ZrO2 -based restorations and lithium disilicate and leucite-reinforced glass-ceramics.